Mediterranean fin whales (Balaenoptera physalus) threatened by Dolphin Morbillivirus - Mazzariol, S; Centelleghe, C; Beffagna, G; Povinelli, M; Terracciano, G; Cocumelli, C; Pintore, A; Denurra, D; Casalone, C; Pautasso, A; DI FRANCESCO, Cristina Esmeralda; DI GUARDO, Giovanni (Emerging Infectious Diseases, 2016)
During 2011-2013, dolphin morbillivirus was molecularly identified in 4 stranded fin whales from the Mediterranean Sea. Nucleoprotein, phosphoprotein, and hemagglutinin gene sequences of the identified strain were highly homologous with those of a morbillivirus that caused a 2006-2007 epidemic in the Mediterranean. Dolphin morbillivirus represents a serious threat for fin whales.